PEMBANGUNAN DAN IMPLEMENTASI PORTAL WEBSITE PENYULUHAN PERTANIAN DI BALAI PENYULUHAN PERTANIAN (BPP) LIMBANGAN - Heru Nugroho; Patrick Adolf Telnoni; Pramuko Aji; Robbi Hendriyanto; Bayu Rima Aditya; Pikir Wisnu Wijayanto; Wawa Wikusna (Jurnal Abdimas Bina Bangsa, 2023)
Particularly in emerging nations like Indonesia, agriculture plays a significant role in a country's economy. However, farmers frequently encounter a variety of difficulties when trying to increase the quantity and caliber of their agricultural output. Limited access to agricultural extension services is one aspect that has an impact on farmers' capacity to obtain agricultural information and technologies. One of the organizations responsible for helping farmers in the area with agricultural extension services is the Limbangan Agricultural Extension Center (BPP). Currently, BPP Limbangan provides information to farmers using traditional extension methods including lectures and printed pamphlets. However, this approach has limitations in terms of information originality, engagement, and reach. To improve farmers' access to agricultural knowledge and technology, the creation and deployment of a multimedia agricultural extension online portal at BPP Limbangan may be a good solution. Farmers will be able to access the most recent information, useful tips, video tutorials, and other agricultural resources online with the help of the website portal. An agricultural extension multimedia website portal can be created to offer a variety of content, including educational articles, films of farming practice demonstrations, details on managing pests and diseases, up-to-date agricultural technology, and advice on growing a farm business. The portal may also offer a discussion board where farmers may exchange stories, ask questions, and engage with agricultural extension agents. Farmers in the BPP Limbangan region should now have simpler and quicker access to agricultural knowledge and technology thanks to the availability of the agricultural extension multimedia online portal. It is anticipated that doing this will improve farmers' management abilities and knowledge, boosting output and quality of agricultural goods